The emergent role of mitochondrial RNA modifications in metabolic alterations - Boughanem Lakhal, Hatim; Böttcher, Yvonne; Tomé-Carneiro, João; López de las Hazas, María-Carmen; Dávalos, Akin Cayir; Macías-González, Manuel (Wiley, 2022)
Mitochondrial epitranscriptomics refers to the modifications occurring in all the different RNA types of mitochondria. Although the number of mitochondrial RNA modifications is less than those in cytoplasm, substantial evidence indicates that they play a critical role in accurate protein synthesis. Recent evidence supported those modifications in mitochondrial RNAs also have crucial implications in mitochondrial-related diseases. In the light of current knowledge about the involvement, the association between mitochondrial RNA modifications and diseases arises from studies focusing on mutations in both mitochondrial and nuclear DNA genes encoding enzymes involved in such modifications. Here, we review the current evidence available for mitochondrial RNA modifications and their role in metabolic disorders, and we also explore the possibility of using them as promising targets for prevention and early detection. Finally, we discuss future directions of mitochondrial epitranscriptomics in these metabolic alterations, and how these RNA modifications may offer a new diagnostic and theragnostic avenue for preventive purposes.
Keywords: Metabolismo; Epitranscriptomics; Metabolic alterations; Metabolism,; Mitochondria; RNA modifications